Neurological manifestations of Kawasaki disease and multisystem inflammatory syndrome in children associated with COVID-19: A comparison of two different clinical entities - Mauro, A.; Di Mari, C.; Casini, F.; Giani, T.; Sandini, M.; Biondi, L.; Calcaterra, V.; Zuccotti, G. V.; Bernardo, L. (Frontiers in Pediatrics, 2023)
Kawasaki disease (KD) is one of the most frequent idiopathic vasculitis in children, affecting medium- and small-sized vessels. Multisystem Iperinflammatory Syndrome in children (MIS-C) associated with COVID-19 has recently emerged as a new systemic hyperinflammatory condition affecting children some weeks after an acute COVID-19 infection. KD and MIS-C share different aspects, and differ in many others: patients affected by MIS-C are usually older, with prominent gastrointestinal manifestations, diffuse adenopathy, extensive conjunctivitis, myocardial damage, leukopenia and thrombocytopenia at the laboratory exams. Both conditions can present neurological complications. The aim of this manuscript is to provide a narrative review of neurological involvement in KD and MIS-C. A comprehensive review literature has been performed and main clinical features analyzed, contributing to neurological differential diagnosis